2008
DOI: 10.1111/j.1600-051x.2008.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive effect of chlorhexidine in ultrasonic instrumentation of aggressive periodontitis patients: a pilot study

Abstract: The adjunctive professional use of CHX formulations to UMI seems to produce no additional effects over UMI alone during supportive therapy in G-AgP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 64 publications
4
33
1
6
Order By: Relevance
“…These results may be ascribed to the combined effect of the professional plaque removal and the stringent patient‐performed regimen aimed at supragingival plaque control. Consistently with these observations, we have demonstrated previously that UMI either with or without additional professional use of CHX may provide a significant reduction of PlI and GI during SPT in G‐AgP patients (Guarnelli et al 2008). In addition, we also observed that the home‐based use of an AmF/SnF 2 ‐containing mouthrinse following conventional mechanical oral hygiene procedures in G‐AgP patients was more effective in controlling the extent of supragingival plaque and gingivitis compared with a placebo (Guarnelli et al 2004).…”
Section: Discussionsupporting
confidence: 87%
“…These results may be ascribed to the combined effect of the professional plaque removal and the stringent patient‐performed regimen aimed at supragingival plaque control. Consistently with these observations, we have demonstrated previously that UMI either with or without additional professional use of CHX may provide a significant reduction of PlI and GI during SPT in G‐AgP patients (Guarnelli et al 2008). In addition, we also observed that the home‐based use of an AmF/SnF 2 ‐containing mouthrinse following conventional mechanical oral hygiene procedures in G‐AgP patients was more effective in controlling the extent of supragingival plaque and gingivitis compared with a placebo (Guarnelli et al 2004).…”
Section: Discussionsupporting
confidence: 87%
“…Although chlorhexidine is considered the most efficient antimicrobial agent for supragingival plaque control, its use as an irrigant in combination with subgingival ultrasonic instrumentation (SUI) is not associated with additional clinical and microbiological benefits [79]. Povidone-iodine has a beneficial effect as a solution for subgingival irrigation [10, 11]; however, the antiseptic is associated with an increased risk of hypersensitivity reaction, and its prolonged use is associated with thyroid dysfunction and staining of the tooth surface and mucosa [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Although chlorhexidine is considered the most efficient antimicrobial for supragingival plaque (P) control, its use as irrigant with subgingival ultrasonic instrumentation did not promote additional clinical benefits (Taggart et al 1990, Reynolds et al 1992, Guarnelli et al 2008. This application can be achieved with the use of ultrasonic instrumentation irrigated with antiseptics.…”
mentioning
confidence: 99%